From Closed Societies to the Open Society : Parochial Altruism and Christian Universalism - Palaver, Wolfgang (Can we survive our origins?, 2015)
Recent research on human altruism has shown that altruism often relies on a common enmity vis--vis other groups, which strengthens internal cohesion. Today this typical pattern of human solidarity is called ?parochial altruism,? and it is seen as referring back to the origin of human civilization. The French philosopher Henri Bergson mentions such a pattern in his description of closed societies, representing the first stage of human evolution. According to Bergson, closed societies were characterized by a static religion fostering a parochial altruism. With the help of Ren Girard?s mimetic theory it is not too difficult to interpret these societies